PHYSICAL RISKS AFFECTING OCCUPATIONAL HEALTH AND SAFETY: TILE PRODUCTION EXAMPLE - GÖKÇEK YILMAZ, Berrin (Atlas Journal, 2020)
The aim of this study is to investigate the physical risks which affects occupational health and safety in ceramic tile production and to present solutions to the identified health and safety risks. Ceramic tiles are floor or wall coverings obtained by mixing the inorganic raw materials such as clay, quartz, feldspar, marble in certain proportions and after shaping in desired sizes, fired glazed or unglazed, patterned or un-patterned. The ceramic tile production is in a very hazardous class according to the Hazardous Class List on Occupational Health and Safety with the production processes and input raw materials. The risk of occupational diseases is very high in the sector. Therefore, it is important to take preventive and preventive measures to investigate the specific risk factors of the sector in order to protect employees from occupational diseases. Within the scope of the study, the physical risk factors such as dust, noise, thermal comfort, lighting and vibration encountered in the ceramic production processes are explained and their effects on health and safety are emphasized and protective measures are addressed. When the physical risk factors are evaluated in the ceramic tile sector, it is seen that raw materials such as quartz and marble are important source of dust and cause occupational diseases, and production departments such as mass production, pressing and rectifying are the sources of noise and vibration.